Economies of network industries - Gottinger, Hans-Werner. (London ; New York : Routledge, 2003)
This book emphasizes policy-level analysis and strategic considerations at the microstructure of industry and its aggregate effects on economic growth, factor productivity, and the business cycle.
Includes bibliographical references and index.
rpm 20/05/14
Loans
Keywords: Business networks; Strategic alliances (Business)